Physical functioning outcome measures in the lumbar spinal surgery population and measurement properties of the physical outcome measures: protocol for a systematic review - Alison B Rushton; Jai Mistry; Michael J Lukacs; Katie L Kowalski; Maren Goodman (BMJ Open)
Introduction Low back pain can lead to substantial decline in physical functioning. For disabling pain not responsive to conservative management, surgical intervention can enhance physical functioning. Measurements of physical functioning include patient-reported outcome measures and physical outcome measures using evaluations of impairments, performance on a standardised task or activity in a natural environment. Selecting outcome measures with adequate measurement properties is fundamental to evaluating effectiveness of interventions. The purpose of this systematic review is to identify outcome measures (patient reported and physical) used to evaluate physical functioning (stage 1) and assess the measurement properties of physical outcome measures of physical functioning (stage 2) in the lumbar spinal surgery population.Methods and analysis This protocol aligns with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines and Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. Using a two-staged approach, searches will be performed in MEDLINE, EMBASE, Health and Psychosocial Instruments, CINAHL, Web of Science, Scopus, PEDro and the grey literature from inception until 15 December 2021. Stage 1 will identify studies evaluating physical functioning with patient-reported or physical outcome measures in the lumbar spinal surgery population. Stage 2 will search for studies evaluating measurement properties (validity, reliability, responsiveness) of the physical outcome measures identified in stage 1 in the lumbar spinal surgery population. Two independent reviewers will evaluate studies for inclusion, extract data, assess risk of bias (COSMIN risk of bias tool and checklist) and quality of evidence (modified Grading of Recommendations Assessment, Development and Evaluation approach). Results for each measurement property per physical outcome measure will be quantitatively pooled if there is adequate clinical and methodological homogeneity or qualitatively synthesised if there is high heterogeneity in studies.Ethics and dissemination Ethics approval is not required. Results will be disseminated through peer-reviewed journal publication and conference presentation.PROSPERO registration number CRD42021293880.